(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2023)
Monkeypox virus appeared in the countries of Central and West Africa. Two distinct species have been identified, the West African type and the Congo type, also known as the Central African type.In the outbreak of monkeypox was first discovered in 1958, while the first human case of the disease was diagnosed in 1970 in the Republic of the Congo in a 7-year-old child. The incubation period ranges from 5-21 days.Monkeypox is transmitted to humans by contact with the virus that causes it through;Mouth and contact with infected animals, including mice, rats, and squirrels, common for monkeypox transmission in Africa, during animal bites from infected animals to humans. Touching the fur or skin of animals, or what comes out of them from blood or bodily fluids. In the case of monkeypox, the virus is transmitted from the mother to the fetus. The main symptoms of monkeypox are similar to the symptoms of smallpox, but they are milder, with the only difference being swollen lymph nodes, fever, headache, backache, cough, sore throat, stuffy nose, fatigue, exhaustion and sweating. The rash of monkeypox begins to appear after 1 - 3 days from the patient with fever, which appears on the face first, then the body begins to spread to the rest of the parts, such as the hands, legs, inside the mouth, genitals, conjunctiva, and the cornea. A complication of monkeypox is Secondary bacterial infection, such as pneumonia, encephalitis, and eye infection.